Edukasi Efek Protektif dan Pemeriksaan Kadar High Density Lipoprotein Terhadap Perlemakan Hati Pada Masyarakat Desa Awila Kabupaten Konawe Utara - Atmaja, Ratih Feraritra Danu; Orno, Theosobia Grace; Hasan, Fonnie Esther (Poltekkes Kemenkes Kendari, 2024)
Low high density lipoprotein level is one of the dyslipidemia conditions that can increase the risk of non-alcoholic fatty liver. Public knowledge about the different functions of fat components, especially HDL, is important to reduce the incidence of fatty liver including other complications such as metabolic syndrome and cardiovascular-related diseases. This activity aims to educate the public about the function of HDL as well as determine the HDL levels of each individual. This activity involved a team of lecturers, students of Poltekkes Kemenkes Kendari, media and 40 community members of Awila Village, Molawe District, North Konawe Regency as participants. This activity includes education, interactive discussions and checking community HDL levels. From the results of the activity, the post-education post-test results increased to 65% from 45% in the pre-test. The HDL level check showed that 55% of the participants had low HDL levels. Educational activities regarding the protective function and food sources high in HDL still need to be done in the community to improve the mindset related to fat and increase public awareness of the complications caused by the disease.